Telomere biology and age-related diseases - Herrmann, Markus; Pusceddu, Irene; März, Winfried; Herrmann, Wolfgang (Clinical chemistry and laboratory medicine, 2018)
Telomeres are the protective end caps of chromosomes and shorten with every cell division. Telomere length has been proposed as a biomarker of biological age and a risk factor for age-related diseases. Epidemiologic studies show an association between leukocyte telomere length (LTL) and mortality. There is solid evidence that links LTL with cardiovascular disease. Short telomeres promote atherosclerosis and impair the repair of vascular lesions. Alzheimer’s disease patients have also a reduced LTL. Telomeres measured in tumor tissue from breast, colon and prostate are shorter than in healthy tissue from the same organ and the same patient. In healthy tissue directly adjacent to these tumors, telomeres are also shorter than in cells that are more distant from the cancerous lesion. A reduced telomere length in cancer tissue from breast, colon and prostate is associated with an advanced disease state at diagnosis, faster disease progression and poorer survival. By contrast, results regarding LTL and cancer are inconsistent. Furthermore, the majority of studies did not find significant associations between LTL, bone mineral density (BMD) and osteoporosis. The present manuscript gives an overview about our current understanding of telomere biology and reviews existing knowledge regarding the relationship between telomere length and age-related diseases.